PERIODONTAL DISEASE : A RISE IN PREVALENCE IN MILITARY TROOPS PENYAKIT PERIODONTAL - Amaliya, Amaliya; Pribadi, Snataka; Akbar, Yun Mukmin; Sitam, Suhardjo (Faculty of Dentistry, Universitas Islam Sultan Agung, 2021)
Background: Oral condition is one of substantial factors in general health. Good oral health will determine dental fitness or readiness in military troops. Oral diseases affecting soldiers may have negative impacts in readiness on deployment or fight and contributes to lowering morale among personnel. At the recruitment stage, the prevalence of periodontal disease is low and controlled before the commencement of the training. As a matter of fact, periodontal health was not considered to be maintained and found to be worsening through the course of time. In the end, many of soldiers were found to suffer from periodontal diseases. Method : This review article aims to discuss several factors in military way of life related to oral condition.Result : Lack of oral hygiene practices, stress, deficiency of nutritious food, and smoking among military personnel may contribute to the prevalence of periodontal disease. Several attempts should be incorporated in military life to reduce the negative impacts of these factors on oral health.Conclusion: Periodontal therapy should be provided early in the military careers and repeated at intervals specific to the needs of each personnel. Several risk factors contributing to the development and severity of periodontal disease should be assessed and overcome to arrest the progression of the disease.